Tata Kelola Percepatan Penanggulangan Kemiskinan di Jawa Tengah (Studi Kasus Kota Semarang) - Budiati, Lilin (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2017)
This study is aimed to examinate and anlalyse the governance of poverty countermeasure acceleration in Central Java Province with Semarang City as the case study. The policy of poverty countermeasure acceleration was realized through the Presidential Regulation No. 15/2010, which was followed up with Minister of Internal Affairs Regulation No. 42/2010. This study is a developmental study with qualitative approach by using primary and secondary data. Ressearch findings were interpreted by futuristic approach to describe the future reality that will be constructed. The research results show that: (1) The governance of poverty countermeasure acceleration has not been vertically and horizontally integrated yet; (2) Coordination which will be developed through TKPK formation at the provincial, city/district level has not been realized yet because of procedural conflict; (3) The poverty countermeasure acceleration program has not been oriented yet to production, trading, and investment activities in the free market place; (4) The solution of governance problem is an effective team formation by the Governor oc Central Java Province.